PENGARUH DOSIS GULA DAN PENAMBAHAN EKSTRAK TEH HITAM TERHADAP FERMENTASI DAN PRODUKSI NATA DE COCO - Lusi, Lusi; Periadnadi, Periadnadi; Nurmiati, Nurmiati (Metamorfosa: Journal of Biological Sciences, 2017)
The purpose of this study was to look at the effect of sugar dose, black tea extract dose, interaction of sugar and black tea exstract dose on the fermentation and production of nata de coco. Completely Randomized Design (CRD) in Factorial was used in this experiment with sixteen treatments and two replications. The first factor was the doses of sugar and the second factor was doses of black tea extract. The results of this study showed that the doses of sugar and addition of black tea extract was able to increase the production of nata de coco. The best dose of sugar in 50 g/ l, the best dose of black tea extract in 8 g/ l. The interaction of sugar dose and black tea extract dose contained in the treatment a1b2 the dose of sugar 50 g/l and black tea extract 8 g/l with an average weight of 23,43 g nata de coco. The benefits of this research is to increase production and quality of nata for the nata de coco’s industry.
Keywords: Nata de Coco, Acetobacter xylinum, black tea extract, the dose of sugar, alcaloids, fermentation